Politics and Public Opinion in Max Weber - Edith Hanke (Historicka Sociologie, 2025)
Social media now strongly determine public opinion, while traditional media, especially newspapers, are losing influence. Max Weber was aware of the power of public opinion. As a sociologist, he presented an extensive project outline for the study of the newspaper industry at the First German Sociologists’ Conference in 1910. As a bourgeois intellectual, he tried to actively influence the formation of public opinion through newspaper articles and political speeches. However, the tension between politics and public opinion remains a blind spot in Max Weber’s political sociology because of his sudden death. My contribution goes in search of traces. At issue are central questions particularly relevant in modern mass democracies: Who has the official ‘mandate’ to form and represent public opinion? How much publicity is wise in terms of state policy? What power does public opinion have in relation to the legitimacy of political systems?